Tokyo ever after - Jean, Emiko (New York : Flatiron Books, 2021)
After learning that her father is the Crown Prince of Japan, Izumi travels to Tokyo, where she discovers that Japanese imperial life--complete with designer clothes, court intrigue, paparazzi scandals, and a forbidden romance with her handsome but stoic bodyguard--is a tough fit for the outspoken and irreverant eighteen-year-old from northern California.
Keywords: Japanese Americans -- Fiction; Belonging -- Fiction; Families -- Fiction; Duty -- Fiction; Princesses -- Fiction; Japan -- Fiction; California -- Fiction